A Case Study of the Evaluation of Slip Surfaces using Mineralogical, Chemical, and Physical Tests - OZAWA, Sachihiko; OHTUBO, Syunsuke; OKAWARA, Masafumi; TERAMURA, Tamotsu; HOTTA, Yoshinori; KUBO, Rina; SATO, Tatsuya (International Journal of Erosion Control Engineering, 2024)
Abstract Identifying the slip surface in a landslide area is one of the most important tasks for evaluating the scale of countermeasures. Conventionally, a slip surface is identified by a combination of visual observations of borehole cores and dynamic observations using pipe strain gauges in the borehole. However, during the limited investigation period, landslides can stop sliding either temporarily or for a long period after a sudden change, such as earthquake-induced landslides, for which identification of the slip surface is currently based only on visual observations of the cores. In this study, the slip surface was identified by conducting various laboratory tests on the “Tanomoki landslide,” where no apparent landslide movement was observed, using pipe strain gauges. Evidence of the slip surface was obtained by using data from an X-ray diffraction analysis, chemical analysis, physical tests, and an improved swelling pressure test based on an oven-drying method. The data properties obtained allowed us to identify an objective and a topographically consistent slip surface, thus providing an example of slip surface determination.